Papaya peel extract as potential corrosion inhibitor for Aluminium alloy in 1 M HCl: Electrochemical and quantum chemical study - Namrata Chaubey; Vinod Kumar Singh; M.A. Quraishi (Ain Shams Engineering Journal, 2018)
This paper deals with the corrosion inhibition effect of Papaya peel extract (PPE) on Aluminium alloy (AA) in 1 M HCl. The corrosion tests were performed by using electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization techniques (PDP). Maximum inhibition efficiency observed is 95.5% and 98.1% from EIS plot and PDP studies at higher concentration (2.0 g L−1) of PPE. Potentiodynamic polarization result shows mainly the cathodic type inhibition for PPE. Surface morphology of AA is carried by scanning electron microscopy (SEM) and atomic force microscopy (AFM). Quantum chemical study is complemented well with the experimental findings of the corrosion inhibition. Keywords: Aluminium alloy, EIS, Corrosion inhibition, SEM, AFM